Analysis of the Level of Larvae Aedes Aegypty with the Risk of Transmission of Dengue Hemorrhagic Fever - Pius Kopong Tokan; Maria Salestina Sekunda (JURNAL KESEHATAN PRIMER, 2019)
Background: Dengue Hemorrhagic Fever (DHF) has caused health problems in Ende Regency, there were 121 DHF cases, 30 of them reside in the Ende City Health Center area. One of the suspected factors is the high population of Aedes aegypti larvae. Therefore it is necessary to analyze the level of Aedes aegypty larvae density to estimate the risk of dengue transmission in Ende City Health Center in 2018. Method: This type of research is a secondary data analysis, the population is data houses / buildings and clean water reservoirs declared positive Aedes larvae aegypti results of examination of Ende City Health Center in 2017 with saturated sampling method The research was conducted at the Ende City Health Center in August 2018. Result: Analysis of Aedes aegypty larvae level using House Index (H1) indicator 36% means that the house / building being examined is included in the high risk category because HI> 5% Contener Index (CI) 21% means that the water reservoir being examined is included in the risk category high because CI> 5%, Breteau Index (BI) 52% means positive water catchment sites of all houses / buildings being examined are included in the high risk category because BI> 50% These three indicators are then linked to the Density Figure (DF) indicator then the City Health Center is included in the area with larvae level is high because DF is 6. Conclusion: Ende City health center is an area with a high risk of transmission of dengue in 2018.